Solubility Enhancement of Embelin by Complexation with Beta Cyclodextrin - Kani, Jashna K; Xavier, Elizabeth N (Indian Journal of Pharmaceutical Education and Research, 2021)
Introduction: Embelin, a phytoconstituent obtained from Embelia ribes of the Myrsinaceae family, has anti-cancer, anti-inflammatory, anti-bacterial, anti-fertility, analgesic, antidiabetic, anti-depressant and wound healing activities. It is hydrophobic in nature leading to low bioavailability. Aim: The present study aims to improve the water solubility and rate of dissolution of Embelin by complexation with β-cyclodextrin. Methods: Inclusion complexes were prepared by physical mixture, kneading and co-precipitation methods. Characterization of complexes was carried out by Fourier-Transform Infrared (FT-IR) spectroscopy and in vitro dissolution study. Differential scanning calorimetry (DSC) and Scanning electron microscopy (SEM) was used to analyze the prepared complexes prepared by the co-precipitation method. Antimicrobial studies of complexes against Staphylococcus aureus and Escherichia coli were carried out by colony counting method. Results: Phase solubility study showed Embelin forms complex with β-cyclodextrin in the ratio 1:2. FT-IR studies of complexes confirmed Embelin forms complex with β-cyclodextrin. DSC and SEM also confirmed the formation of a complex of Embelin with β-cyclodextrin. In vitro dissolution studies showed that the time to release 50 % (t50) of Embelin was in the order 15 min, 30 min, 60 min for complexes prepared by coprecipitation, kneading method and physical mixture respectively. Complexes prepared by the coprecipitation method showed 2 log reductions in the number of S. aureus and 1 log reduction in the number of E. coli in comparison with Embelin. Conclusion: Complexes of Embelin prepared by co-precipitation method resulted in largest percent drug content, enhanced aqueous solubility and antibacterial activity.
Keywords: Embelin; β-cyclodextrin; Inclusion complexes; Solubility; Co-precipitation; method